Bacteria are microbes which have an ability to live wherever there is a life. Some of the bacteria are saprophyte and some are parasitic. But most of the bacteria have not been identified or cultured; therefore the benefits are still unknown. Methanogenic bacteria are one of the saprophyte bacteria. These bacteria produces methane, a biogas as an alternative fuel in the future. Most of methanogenic bacteria are uncultured, however a few of them are found in the sewage of coconut water. The o - Ardi Kapahang; Maria Bintang; D.D. Sastraatmadja; Dedy Duryadi Solichin (Forum Pasca Sarjana, 2007)
Bacteria are microbes which have an ability to live wherever there is a life.  Some of the bacteria are saprophyte and some are parasitic. But most of the bacteria have not been identified or cultured; therefore the benefits are still unknown.  Methanogenic bacteria are one of the saprophyte bacteria. These bacteria produces methane, a biogas as an alternative fuel in the future.  Most of methanogenic bacteria are uncultured, however a few of them are found in the sewage of coconut water.  The objectives of this research are to isolate, characterize and identify the methanogenic bacteria that lived in coconut water.  The method of this research was fermentation, analysis characterization, and identification of methanogenic bacteria. First, methanogenic bacteria were isolated from coconut water by fermentation.  The samples were from four places in Minahasa, which are Rasi (I), Koka (II), Amurang (III), and Lola (IV) and one place in Bogor (V). Secondly, the methane produced from fermentation was analysed by gas chromatography and the bacteria can be characterized by Bergey’s method. The next step is the identification which was conducted by isolating  the DNA, amplifying the DNA by PCR, then sequencing the DNA with BioEdit Sequence Aligment.  As the result, high and stable  methane was produced in Rasi (I) and Amurang (III). The characteristic of the bacteria are red colony (M) and white colony (P). The shape of the colonies is circles, gram positive, basil shape, mesofile, positive of catalase and citrate, positive of sugar fermentation, gelatin, casein and starch hydrolysis also lived in Nutrient Broth with pH 5.7-6.8.  The sequencing of isolate P resulting in nucleotide  composition of G 31.25%, C 20.58%, A 27.11% and T 21.04%  while isolate M are   G 31.34%, C 20.31%, A 27.02% and T 21.32%.  The identification of isolate M is equal with Clostridium tyrobutyricum (100 %) and isolate P is very close with Clostridium tyrobutyricum (99 %).   Key words: bacteria, methane, coconut water